Analisis Kemampuan Pemecahan Masalah Matematis Siswa Berdasarkan Disposisi Matematis - Uuf Muflihatusubriyah; Rukmono Budi Utomo; Nisvu Nanda Saputra (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2021)
This study aims to describe students' mathematical problem-solving abilities based on mathematical dispositions at Riyadlul Mukhlishien Middle School. This type of research used in this research is descriptive qualitative. The research subjects used were 21 students of class VIII A. The data sources of this research are in the form of questionnaires, test descriptions and interviews. The results of the questionnaire were used to classify the level of students' mathematical dispositions. After that, two students from each category of mathematical disposition were selected to be the subject of tests and interviews. The results of tests and interviews of mathematical problem-solving abilities were analyzed based on the mathematical disposition of the students. The results of this study indicate that the mathematical disposition of SMP Riyadlul Mukhlishien students is divided into three categories, high, medium and low. Students who have mathematical problem-solving abilities in the high mathematical disposition category are able to meet the indicators of mathematical problem-solving abilities well and write them down completely. Students who have mathematical problem-solving abilities in the moderate mathematical disposition category are able to meet the indicators of mathematical problem-solving abilities but do not write them down completely. Students who have mathematical problem-solving abilities in the low mathematical disposition category are less able to meet the indicators of mathematical problem-solving abilities because they do not write them down completely and still experience errors in calculations